The Concept of "Smart City" in Assumptions of Urban Development Policy – Polish Perspective - Sikora-Fernandez, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Smart city can be considered as a territory with high capacity for learning and innovation, creative, with research and development institutions, higher education, infrastructure and digital communication technologies, as well as a high level of management performance. Cities can therefore be defined as "smart", they have human and social capital, traditional and modem communication infrastructure (transport, respectively, and communication technologies), the development is consistent with the theory of sustainable development and participatory governance ensures better quality of life. The purpose of this article is to attempt to answer the question of how Polish cities meet the criteria for the concept of smart cities, and how the implementation of this concept is reflected in the Polish documents relating to the development of the country and cities.